БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИ МУСТАҚИЛ ФИКРЛАШГА ТАРБИЯЛАШ МАСАЛАСИ - Бабашева, Г.Б. (SCIENCE and SOCIETY, 2022)
This article talks about the focus of primary school students on independent thinking and its pedagogical and psychological features.